Youth exposure to smoking in the home and in cars: how often does it happen and what do youth think about it?. Issue 2 (19th February 2008) - Leatherdale, S T; Smith, P; Ahmed, R
Abstract : Aim: Little is known about what youth think about restricting smoking in their homes or in cars. The present study characterises the frequency of youth being exposed to smoking in their homes and cars, and the beliefs that youth have about restricting people from smoking around youth in those locations. Methods: Data from the 2004 Youth Smoking Survey (YSS) were used to examine youth exposure to smoking and beliefs about smoking in the home and car among 29 243 Canadian youth in grades 5–9. Logistic regression models were conducted to examine if being exposed to smoking at home or in the car were associated with the beliefs youth have about either smoking around children at home or smoking around children in cars. Results: In 2004, 23.1% of youth in grades 5–9 were exposed to smoking in their home on a daily or almost daily basis, 26.3% were exposed to smoking while travelling in a car at least once in the previous week. The majority of youth reported that they do not think smoking should be allowed around children at home (90.6%) or in cars (90.2%). Males were more likely than females to report that smoking should not be allowed around children at home (OR 1.38) or in cars (OR 1.39). Youth living in a house where someone smokes inside daily were more likely to report that smoking should not be allowed around children at home (OR 1.20) or in cars (OR 1.21). Youth living in a house where the rules do not prevent people from smoking inside were also more likely to report that smoking should not be allowed around children at home (OR 2.07) or in cars (OR 1.76). Youth who have ridden in a car with someone who was smoking cigarettes in the past 7 days were more likely to report that smoking should not be allowed around children in cars (OR 1.73). Conclusions: It is common for Canadian youth to be exposed to SHS in their homes or while in cars on a frequent basis even though the vast majority of youth do not think smoking should be allowed around children in those locations. This new evidence suggests that programs and policies designed to prevent individuals from smoking around youth in these locations should be a public health priority.